Investigation of spatial distribution of metal vapours admixtures in the plasma of an electric arc discharge - Murmantsev, A. (Problems of Atomic Science and Technology, 2023)
This work focuses on diagnosing the plasma in an electric arc discharge in an argon flow using optical emission spectroscopy. The method employed for determining the population of energy levels and the concentration of metal atoms based on the absolute values of emission intensity is described and validated. The experimental setup includes a spectrograph and an RGB CMOS matrix as the emission registration device. By obtaining the absolute values of the spectral radiances of Cu I lines and considering the axial symmetry of the electric arc discharge, the local radiation intensity of these lines is determined. Radial distributions of copper atom concentrations are then calculated using the absolute values of emission intensities and the radial distribution of the excitation temperature, which is determined using the Boltzmann plots technique. Two methods are employed for calculating the atom concentra ions. The first method involves Boltzmann plots based on four spectral lines of Cu I and the corresponding excitation temperature. The second method determines the concentrations directly from the population of copper’s energy levels, which are derived from the absolute values of emission intensity of the Cu I spectral lines. The results obtained from these two methods exhibit a coincidence of within 20%, supporting the recommendation of this technique for plasma diagnostics in electric arc discharges. Робота присвячена діагностиці плазми електродугового розряду в потоці аргону методами оптичної емісійної спектроскопії. Описано та апробовано метод визначення заселеності енергетичних рівнів та концентрації атомів металу із абсолютних значень інтенсивності випромінювання спектральних ліній. Дослідження проводили з використанням спектрографа та RGB CMOS матриці як пристрою реєстрації випромінювання. Отримано абсолютні значення спектральної яскравості ліній Cu I, та з урахуванням осьової симетрії електродугового розряду визначено їх локальну інтенсивність випромінювання. Із залученням абсолютних значень інтенсивності випромінювання та радіального розподілу температури заселення, визначеної методом діаграм Больцмана, отримано радіальні розподіли концентрацій атомів міді. Розглянуто два методи розрахунку концентрації атомів. А саме, розрахунок із діаграми Больцмана на основі чотирьох спектральних ліній Cu I та визначеної температури заселення. З іншого боку, концентрацію отримано із заселення енергетичних рівнів міді, визначених безпосередньо із абсолютних значень інтенсивності випромінювання цих спектральних ліній Cu I. Результати, отримані цими двома методами, збігаються в межах 20%, що дає підстави рекомендувати дану методику для діагностики плазми електродугових розрядів.